Genetic and Cellular Basis of Resistance to Black Rot Caused by Xanthomonas campestris pv. campestris in Brassica rapa - Siping Deng; Congcong Kong; Hongxue Ma; Jialei Ji; Yong Wang; Yangyong Zhang; Mu Zhuang; Limei Yang; Zhiyuan Fang; Vasiliy Taranov; Anna M. Artemyeva; Honghao Lv (Horticulturae)
Brassica crops, cultivated as vegetables, oilseeds, and forages, are vital economic resources in agricultural production. However, black rot caused by Xanthomonas campestris pv. campestris (Xcc) poses a significant threat to the production of these crops. This study aimed to enhance the resistance resource pool for Brassica crops by evaluating 29 inbred lines and 52 commercial cultivars of B. rapa through an inoculation test. Among these, 11 inbred lines, such as ‘E5’ and ‘LW’, and 8 commercial cultivars, such as ‘QX’ and ‘SY’, demonstrated high resistance. We constructed a genetic segregating population (P1, P2, F1, F2) using the highly resistant line ‘E5’ and the highly susceptible line ‘E4’ as parents. Utilizing a major gene plus polygenic mixed inheritance model for genetic analysis, our findings indicate that the resistance to black rot in ‘E5’ is governed by a pair of additive-dominant polygenes, and the main gene heritability is 93.43%. Furthermore, transmission electron microscopy examination revealed numerous autophagic structures in the xylem parenchyma cells of the highly resistant line ‘E5’, while the highly susceptible line exhibited cell necrosis, indicating that the resistant material might protect mesophyll cells and adjacent structures through programmed cell death. This research contributes novel genetic materials for breeding disease-resistant varieties, enhances our understanding of Xcc invasion mechanisms and host defense traits, and establishes a theoretical framework for the effective prevention and control of these diseases.